2019
DOI: 10.3390/admsci9040075
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Practices and Innovation Outcomes: The Moderating Role of Risk-Taking and Proactiveness

Abstract: This study, by the application of a linear regression by ordinary least squares (OLS), aimed to explore the relationships between knowledge management practices (KMP) and innovation outcomes (product, process, organizational, and commercial), and how they can be moderated by two dimensions of the entrepreneurial orientation (proactiveness and risk taking). This empirical study used survey data from a sample of 288 Spanish family small and medium enterprises (SMEs). The results revealed a positive effect of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 121 publications
(152 reference statements)
1
16
0
Order By: Relevance
“…The paper reveals that entrepreneurial orientation and intrapreneurship are significantly correlated. Firm entrepreneurial orientation constructs innovativeness, risk-taking and proactiveness are the premises for employee intrapreneurial behaviour (Luu, 2020; García-Piqueres et al , 2019; He and Hui, 2020; Urban and Wood, 2017). Firm entrepreneurial orientation concentrates the influence of the organisational strategy, while intrapreneurial behaviour emphasises the impact of employee traits and characteristics in explaining employee innovation behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The paper reveals that entrepreneurial orientation and intrapreneurship are significantly correlated. Firm entrepreneurial orientation constructs innovativeness, risk-taking and proactiveness are the premises for employee intrapreneurial behaviour (Luu, 2020; García-Piqueres et al , 2019; He and Hui, 2020; Urban and Wood, 2017). Firm entrepreneurial orientation concentrates the influence of the organisational strategy, while intrapreneurial behaviour emphasises the impact of employee traits and characteristics in explaining employee innovation behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also claim that proactiveness and risk-taking attitude are the two key dimensions of EO that shows the relationship with innovation and also enhances the firm's performance (Utami et al, 2021). These results are also supported by other researchers as well, i.e., risk-taking attitude shows a positive impact on the process of innovation and thus upper-level management supports new ideas and also allocates huge resources in the implementation of these ideas (García-Piqueres et al, 2019).…”
Section: Risk Attitude and Innovation Intensitymentioning
confidence: 60%
“…He stressed that it even becomes more relevant when managing construction projects, because these kinds of projects are usually more technical and complex in nature; requiring enough engineering knowledge and the application of scientific principles. Nonetheless, on a relatively different note, other authors have suggested competencies such as financial management (Michalski et al 2018), organizational governance (Kalodimos 2017) and risk management (García-Piqueres et al 2019;Lozano-Torró et al 2019; Klakegg 2016) as relevant for effective PM.…”
Section: Key Competencies For Effective Project Managementmentioning
confidence: 99%